(3YedjGJ GdJhQb hJWHjbGJgG GdEbJUGOjI aj GdeUGQa GdESdGejIs - (3CMeO agO(B, (3GdQTjOjs ((3YeGf(B:s (3OGQ GdfaGFS(B,s, 2005)
(3eaghe GdJhQb hGdeUWdMGJ GdeJUdI Hg(B-(3GdJhQb Gdabgj(B-(3GdJWHjbGJ GdeUQajI ddJhQb hJLGQHgG aj GdeUGQa GdESdGejI(B-(3GdJbhje Gdabgj hGdEbJUGOj dYedjI GdJhQb aj GdeUGQa GdESdGejIs
Keywords: (3GdJhQbs; (3GdJhQb aj GdeUGQa GdESdGejIs; (3JWHjbGJ GdJhQbs